Implementation of advanced practice nursing in Brazilian Primary Health Care: methodological path - Manoel Vieira de Miranda Neto; Letícia Yamawaka de Almeida; Daiana Bonfim; Talita Rewa; Maria Amélia de Campos Oliveira (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to describe the operationalization of the steps of a model proposed by the Pan American Health Organization for implementing advanced practice nursing in Primary Health Care services. Methods: a methodological study, with a qualitative approach, carried out in a local health system located in southern São Paulo. The first six steps of the model were followed: 1) improve health outcomes; 2) identify stakeholders; 3) determine unmet health needs; 4) identify priorities and goals to introduce advanced nursing practices in primary health care; 5) define advanced practice nursing in primary health care; 6) plan implementation strategies. Results: in each step, the objectives, methodological strategies and operationalization were described. Final Considerations: the model proved to be effective to support the process of development and implementation of advanced practice nursing in the local system studied.